How penetrable are thioalkyl self-assembled monolayers? - Waring, C; Bagot, P; Bebbington, M; Räisänen, M; Buck, M; Costen, M; McKendrick, K (2010)
The depth of penetration of photolytically generated, gas-phase O( 3P) atoms into thioalkyl self-assembled monolayers (SAMs) has been investigated. Custom-synthesized, site-selectively deuterated SAMs were prepared on Au substrates and characterized by scanning tunneling microscopy (STM). Relative yields of gas-phase OD were detected by laser-induced fluorescence (LIF). Reaction was suppressed at the terminal CD3 by the higher abstraction barriers for primary D atoms, yielding only 16 ± 3% of the total OD. The C2 (first secondary) site is the individually most reactive (42 ± 5%). The remaining significant contribution (42 ± 4%) from positions as deep as C3-C6 is a considerable surprise when compared with previous related experiments using higher-energy O+ ion projectiles and detecting OH- products. The apparent greater penetrability of the SAM layer found here may have prior theoretical support. Furthermore, we show that NO2 damages the surfaces but that C12 SAMs are considerably more resistant than C6 SAMs. © 2010 American Chemical Society.